PENGARUH INTERAKSI GA3 DAN KONDISI LENGAS TANAH TERHADAP PERTUMBUHAN BIBIT BENIH KEDELAI HITAM - Indah Permanasari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
Water is an important factor for plant growth. Water-deficit in soil will affect plant growth and reduce productivity. The objective of this research was to defend seed viability, plant growth, yield, and seed quality on soybean in drought condition using GA3. The research was conducted at, Green House of Agriculture Faculty and Experimental Field of KP4 Gadjah Mada University in Kalitirto, Yogyakarta from September 2006 to January 2007. The research was arranged split-plot design 5x3 factorials with 3 replications. The Major plot was soil moisture content, which arranged in randomized complete block design, consisted of 5 soil moisture content levels; 100, 80, 60, 40, and 20% field capacity. The Sub-plot was the concentration of GA3 with 3 levels: 0, 100, and 200 ppm. The result showed that seedling growth was delayed by the decreasing of soil moisture content. It was revealed that 20% of the soil moisture content and immersion treatment in GA3 at 100 ppm significantly increased the seed vigor. Furthermore, immersion in GA3 at 100 and 200 ppm tends to increase the plant height and its hypothetical index vigor. The treatment also raises the dry-weight of seedling up to 60%. There was a positive correlation between GA3 concentration and leaf area.